STRATEGY OF DEVELOPMENT FREE SCHOOL BUS SERVICES (International Conference on Social and Islamic Studies, 2021)
Makassar as a metropolitan city, transportation is still a problem, especially public transportation for students. To reduce congestion and minimize the use of private vehicles by students, the Makassar City Transportation Service provides free school buses for students. This study aims to determine the quality of service and strategies for developing free school bus services in Makassar City. Data was collected through observation and distributing questionnaires with simple random sampling technique. The analytical method used is descriptive qualitative analysis and SWOT analysis. The results showed the quality of free school bus services with tangible variables (62% in the low category), reliability (54% in the medium category), responses (73% in the high category), assurance (81% in the medium category). very high category) and empathy (77% in high category). Based on the SWOT results, the strategy for developing free school bus services is in quadrant I, namely a rapid growth strategy, by further optimizing the strengths and opportunities of free school buses in Makassar City by increasing the discipline and responsibility of officers through coaching and training, paying attention to the punctuality of leaving and returning home. schools, maintaining the validity of service information to students, maintaining free subsidies from the city government, reducing the use of private vehicles by students by increasing the fleet and school bus routes, increasing efforts to prevent congestion and orderly on roads and school areas as well as equipping facilities and infrastructure for comfort and convenience, school bus safety.